Medication administration made incredibly easy! - Lippincott Williams & Wilkins (Philadelphia, PA : Lippincott Williams & Wilkins, 2003)
Zero in on the principles, practices and procedures that promote safe and accurate drug administration with this text. Features of this title includes succinct reviews of pharmacokinetics and pharmacodynamics, discussion of legal and ethical issues, examples of drug administration documentation, and an entire section on the critical subject of medication errors. Nurse Joy and sidekicks inject levity while imparting critical information, including coverage of drug administration routes and techniques. This text also features clear, lucid explanations of concepts associated with drug administration supported by definitions of key terms and abundant illustrations. Appendices summarize dosage calculation, measurement conversions, controlled drugs, and more.
Includes index.
Keywords: PHARMACEUTICAL PREPARATIONS, administration and dosage; DRUG THERAPY, nursing; DRUG ADMINISTRATION ROUTES